2022
DOI: 10.1038/s41598-022-10527-y
|View full text |Cite
|
Sign up to set email alerts
|

The effects of short-term and long-term air pollution exposure on meibomian gland dysfunction

Abstract: We aim to assess the effects of different air pollutants on meibomian gland dysfunction (MGD). As a prospective multicenter study, 864 patients were recruited from four different regions (i.e., coal, oil, steel, and living). The oil region had a significantly lower temperature and higher O3 and SO2 concentrations than other regions. Notably, participants in oil region presented with more frequent and serious MGD signs and higher cytokine levels (median interleukin 6 [IL-6] in oil: 2.66, steel: 0.96, coal: 0.38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
(59 reference statements)
1
8
0
Order By: Relevance
“…This study found that subjects in highly polluted regions have increased MG expressibility, meibum score and meiboscore, which substantiates the findings of previous epidemiologic studies 44 46 . Some studies have indicated that fine particulate air pollution might influence MG function not only by absorbing the lipid of tear film but also by entering MG, leading to lipid deficiency or maldistribution 47 , 48 . These abnormalities may explain the instability of tear film.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that subjects in highly polluted regions have increased MG expressibility, meibum score and meiboscore, which substantiates the findings of previous epidemiologic studies 44 46 . Some studies have indicated that fine particulate air pollution might influence MG function not only by absorbing the lipid of tear film but also by entering MG, leading to lipid deficiency or maldistribution 47 , 48 . These abnormalities may explain the instability of tear film.…”
Section: Discussionmentioning
confidence: 99%
“…Although UPM is closely related to the clinical symptoms and signs of MGD, 17 the underlying pathological mechanisms remain unclear. This study provided the first experimental evidence of UPM-induced MGD-like changes, including punctate corneal defect, glandular dropout, meibum lipids disorder, and ductal obstruction of MG.…”
Section: Discussionmentioning
confidence: 99%
“… 16 Noticeably, a recent prospective multicenter study reported a positive correlation between UPM exposure and decreasing meibum quality and meibomian gland (MG) dropout frequency, indicating that UPM may also exert a role in MG dysfunction (MGD) pathophysiology. 17 However, the toxic effect of UPM on the MG remains largely unclear, as previous experimental studies primarily focused on its effects on inflammatory responses, proliferation, and apoptosis in corneal 18 , 19 and conjunctival epithelial cells. 20 , 21 …”
mentioning
confidence: 99%
“…Subjects were required to do 3–4 h outdoor activities per day (average) in the corresponding zone. Since the patients were enrolled from the industrial and densely populated areas, the primary sources of PM are the traffic emission, combustion, and sandstorms ( 22 26 ). The PM compositions are predominantly organic compound and inorganic salt (nitrate and sulfate).…”
Section: Methodsmentioning
confidence: 99%